The Gotcha Box - "Cowley , Joy " (Scotland publications)
"The 'Gotcha' Box" is a children's book authored by Joy Cowley, featuring illustrations by Tony Stoddard. This emergent reader is part of "The Story Box" series, specifically designed to support early literacy development. With a word count of just 31 words, the book employs simple, repetitive text to help young readers build confidence and fluency. The narrative centers around a playful scenario involving a box, aiming to engage children while reinforcing basic phonics elements and high-frequency words that have been previously taught.